Crop Performance and Farming Analyses of 'Merah Delima' Papaya and 'California' Papaya on Sub-Optimal Land in Jambi. Issue 1 (1st April 2022) - Edi, S; Purnamayani, R
Abstract: Papaya is a tropical fruit that is in great demand by the community at an affordable price and can adapt to various types of soil, including sub-optimal land. Jambi province has a quite large area of sub-optimal land. The aim of the study was to determine the growth, production, and farming analysis of Merah Delima and California Papaya on sub-optimal land. The research was carried out at the Agricultural Technology Park in Suka Maju Village, Geragai District, East Tanjung Jabung Regency, Jambi. Parameters observed included vegetative and generative plant performance and farming analysis. The results showed that Merah Delima Papaya provided advantages in production parameters, namely the number of fruit and fruit weight. California papaya provides a fruit weight per grain. The analysis of profitable papaya farming has a total profit of Rp. 104, 736, 000, - per hectare for Merah Delima papaya and Rp. 61, 728, 000, - per hectare for papaya California. The results of the analysis of the BC ratio value of 2.95 for the Merah Delima papaya and the BC ratio of 1.95 for the California papaya, indicated that farming of these two papaya varieties provided benefits and would be feasible to cultivate.